HUBUNGAN ANTARA KEBAHAGIAAN DAN PENYESUAIAN DIRI PADA MAHASISWA YOGYAKARTA - Agustin, Firdaus Jana; Nastain, M. (International Journal of Multidisciplinary Research and Literature, 2024)
This study discusses the relationship between happiness, education, and self-adjustment in university students in Yogyakarta. The data collection method used was a survey by distributing questionnaires to respondents. The results showed that happiness has a positive relationship with education and self-adjustment, and education also has a positive relationship with self-adjustment. The research was conducted on university students in Yogyakarta. This paper also provides a solid basis for further research on the same topic by presenting findings that can serve as a foundation for further research. This research explores the concept of happiness, its impact on individuals, and the importance of self-adjustment in achieving happiness. The article also discusses university students' challenges in adapting to a new environment